Building Excellent Human Resources through Merdeka Belajar Kampus Merdeka in Era 5.0 - Rony, Zahara Tussoleha; Widodo, Aan; Lestari, Tyastuti Sri; Saimima, Ika Dewi Sartika; Ismaniah, Ismaniah; Mursito, Kendhy (Universitas Pendidikan Ganesha, 2024)
Welcoming the era of Society 5.0, through the program